1995
DOI: 10.1183/09031936.95.08071100
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-induced late-phase airways obstruction in the pig: mediator release and eosinophil recruitment

Abstract: A Al ll le er rg ge en n--i in nd du uc ce ed d l la at te e--p ph ha as se e a ai ir rw wa ay ys s o ob bs st tr ru uc ct ti io on n i in n t th he e p pi ig g: : m me ed di ia at to or r r re el le ea as se e a an nd d e eo os si in no op ph hi il l r re ec cr ru ui it tm me en nt t ABSTRACT: The aim of this study was to develop a novel model for studies of mediator mechanisms involved in the late asthmatic reaction in the lower airways, by using the sensitized pig. The release of histamine and cysteinyl-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
28
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
8
28
0
Order By: Relevance
“…The changes in Raw, CL,dyn and BVC that were observed in the present study as a result of antigen challenge are in agreement with earlier studies in the pig [15,17]. Moreover, pig anatomy has been found to be suitable for experimental investigations into bronchial circulation [18].…”
Section: Discussionsupporting
confidence: 93%
“…The changes in Raw, CL,dyn and BVC that were observed in the present study as a result of antigen challenge are in agreement with earlier studies in the pig [15,17]. Moreover, pig anatomy has been found to be suitable for experimental investigations into bronchial circulation [18].…”
Section: Discussionsupporting
confidence: 93%
“…They also have mild airway inflammation and ASM hypertrophy or hyperplasia (32). Studies in other laboratories have shown the presence of late pulmonary reactions in sensitized pigs, with suppression of endogenous cortisol (12). In our pig model, the effects of sensitization on lung physiology in vivo are similar to those of several other animal models, including guinea pig (11,16), rat (3), and rabbit (22).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, pigs are outbred, similar to humans, perhaps better mimicking the effect of environmental influences than do inbred mice. The clinical signs of allergy in pigs are similar to those in humans, and several studies have been reported (11,15,16,32,33,35,41).…”
supporting
confidence: 49%